Self-Control And Financial Education Moderate the Effects of Financial Literacy and Materialism on Savings Decisions - Eva Sylvia; Sudarno; Muhammad Sabandi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study uses a quantitative descriptive research type with 395 respondents as undergraduate students of Sebelas Maret University, Surakarta as research subjects. The sampling technique uses probability sampling technique with a proportional random sampling approach. The data collection technique used is documentation and questionnaires. The validity test technique uses Confirmatory Factor Analysis (CFA) and the reliability test technique uses Croanbach's alpha. Data analysis in this study uses descriptive statistics, classical assumption tests (normality test, linearity test, multicollinearity test, and heteroscedasticity test) and hypothesis testing (hierarchical regression test, t-test, and assumption of determination coefficient) with SPSS 25 software. The results of the study show: Financial literacy has a positive and significant effect on saving decisions, Materialism has a negative and significant effect on saving decisions, Self-control cannot moderate the relationship between financial literacy and materialism on saving decisions, Financial education can moderate the relationship between financial literacy and materialism on saving decisions which is reinforced by the results of the study in the discussion.